2009
DOI: 10.1063/1.3192652
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dislocations in wake-type flow induced by spanwise disturbances

Abstract: Vortex dislocations in wake-type flow induced by three types of spanwise disturbances superimposed on an upstream velocity profile are investigated by direct numerical simulations. Three distinct modes of vortex dislocations and flow transitions have been found. A local spanwise exponential decay disturbance leads to the appearance of a twisted chainlike mode of vortex dislocation. A stepped spanwise disturbance causes a streamwise periodic spotlike mode of vortex dislocation. A spanwise sinusoidal wavy distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Intuitively, the extents to which wake structures and behaviour are altered by these cylinders depend heavily not only upon parameters which dictates non-wavy cylinder flows such as Reynolds number, aspect-ratio, end-wall effects, free-stream turbulence level and surface roughness, but also wavelength and wave amplitude as well. Better understanding of how these nodes and saddles affect the canonical flow-past-circular-cylinder scenario has important implications in terms of flow stability analysis [Ling and Zhao (2009), Garbaruk and Crouch (2011)], bluff-body drag reductions and vortex-induced vibrations [Bearman and Owen (1998), Darekar and Sherwin (2001), Lam et al (2004aLam et al ( , 2004b]. Therefore, it should not be surprising that a large number of the above-mentioned studies tried to establish the critical relationships between the resultant wake behaviour, pressure distributions and lift/drag levels.…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, the extents to which wake structures and behaviour are altered by these cylinders depend heavily not only upon parameters which dictates non-wavy cylinder flows such as Reynolds number, aspect-ratio, end-wall effects, free-stream turbulence level and surface roughness, but also wavelength and wave amplitude as well. Better understanding of how these nodes and saddles affect the canonical flow-past-circular-cylinder scenario has important implications in terms of flow stability analysis [Ling and Zhao (2009), Garbaruk and Crouch (2011)], bluff-body drag reductions and vortex-induced vibrations [Bearman and Owen (1998), Darekar and Sherwin (2001), Lam et al (2004aLam et al ( , 2004b]. Therefore, it should not be surprising that a large number of the above-mentioned studies tried to establish the critical relationships between the resultant wake behaviour, pressure distributions and lift/drag levels.…”
Section: Introductionmentioning
confidence: 99%
“…The wake profile at 𝑥 = 2.783, remarkably different from the classical wake profile in the non-wavy cylinder, is very similar to that used in the study of the wake-type flow. [9] The complete suppression of vortex shedding is also observed by introducing the disturbance on the upstream velocity profile. The vertical vorticity as a unique additional vorticity is directly resulted from such disturbance.…”
mentioning
confidence: 93%
“…Darekar and Sherwin (2001) have reported, through their numerical study of the flow over a square cylinder with a wavy stagnation face, a complete suppression of the Karman vortex shedding and about 16% reduction in the total drag with sufficiently steep waviness. Ling and Zhao (2009) introduced spanwise sinusoidal wavy disturbance in a two dimensional periodic wake flow and found that the Karman vortex shedding ceased to exist for a moderate waviness. In both these numerical investigations, the evolution of the streamwise and transverse vorticities was observed in the region of inflection points of the spanwise wavy disturbance thereby weakening the spanwise vorticity of the Karman vortex and causing its dislocation.…”
Section: Introductionmentioning
confidence: 98%